Combination antiretroviral drugs in PLGA nanoparticle for HIV-1 - Sharma Akhilesh (BMC Infectious Diseases, 2009)
Abstract Background Combination antiretroviral (AR) therapy continues to be the mainstay for HIV treatment. However, antiretroviral drug nonadherence can lead to the development of resistance and treatment failure. We have designed nanoparticles (NP) that contain three AR drugs and characterized the size, shape, and surface charge. Additionally, we investigated the in vitro release of the AR drugs from the NP using peripheral blood mononuclear cells (PBMCs). Methods Poly-(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) containing ritonavir (RTV), lopinavir (LPV), and efavirenz (EFV) were fabricated using multiple emulsion-solvent evaporation procedure. The nanoparticles were characterized by electron microscopy and zeta potential for size, shape, and charge. The intracellular concentration of AR drugs was determined over 28 days from NPs incubated with PBMCs. Macrophages were imaged by fluorescent microscopy and flow cytometry after incubation with fluorescent NPs. Finally, macrophage cytotoxicity was determined by MTT assay. Results Nanoparticle size averaged 262 ± 83.9 nm and zeta potential -11.4 ± 2.4. AR loading averaged 4% (w/v). Antiretroviral drug levels were determined in PBMCs after 100 μg of NP in 75 μL PBS was added to media. Intracellular peak AR levels from NPs (day 4) were RTV 2.5 ± 1.1; LPV 4.1 ± 2.0; and EFV 10.6 ± 2.7 μg and continued until day 28 (all AR ≥ 0.9 μg). Free drugs (25 μg of each drug in 25 μL ethanol) added to PBMCs served as control were eliminated by 2 days. Fluorescence microscopy and flow cytometry demonstrated phagocytosis of NP into monocytes-derived macrophages (MDMs). Cellular MTT assay performed on MDMs demonstrated that NPs are not significantly cytotoxic. Conclusion These results demonstrated AR NPs could be fabricated containing three antiretroviral drugs (RTV, LPV, EFV). Sustained release of AR from PLGA NP show high drug levels in PBMCs until day 28 without cytotoxicity.